High-efficiency composite diaphragm for hydrogen production by alkaline electrolysis of water and preparation method of high-efficiency composite diaphragm

The polymer nonwoven fabric is prepared by flash evaporation and the conductive inorganic particles are grown on its surface and inside the pores, which solves the problems of high resistance, large energy consumption and safety hazards of alkaline electrolysis hydrogen production, and achieves efficient and low-cost hydrogen production.

CN119663369APending Publication Date: 2025-03-21HUANENG CLEAN ENERGY RES INST +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411581480.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In actual applications, existing alkaline electrolytic hydrogen-making membranes have problems such as excessive resistance, high energy consumption, difficulty in reducing costs, low hydrogen purity and great safety hazards.

Method used

The polymer nonwoven fabric was prepared as the diaphragm framework by flash evaporation, and conductive inorganic particles were grown on the surface of the nonwoven fabric and inside the pores by in-situ chemical deposition to form a highly efficient composite separator.

Benefits of technology

It effectively reduces the membrane resistance, improves the mechanical strength and the conduction efficiency of hydroxide ions, reduces the hydrogen production energy consumption of the electrolytic cell, and improves the purity of hydrogen, enhancing safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663369A_ABST
    Figure CN119663369A_ABST
Patent Text Reader

Abstract

The invention provides an efficient composite diaphragm for hydrogen production through alkaline electrolysis of water and a preparation method of the efficient composite diaphragm, and belongs to the technical field of hydrogen production through electrolysis of water. The preparation method comprises the following steps: S110, dissolving a polymer raw material in a solvent, stirring and mixing to form a spinning solution; s120, preparing a polymer non-woven fabric from the spinning solution through a flash evaporation method; s130, the polymer non-woven fabric is sequentially soaked in a strong alkali solution and a metal chlorate or metal nitrate solution, and conductive inorganic particles are formed on the surface and in pore channels of the polymer non-woven fabric after roasting; and S140, repeating the step S120 and the step S130 for multiple times, and cleaning the membrane material to obtain the porous composite membrane. The polymer non-woven fabric prepared by adopting a flash evaporation method is used as a diaphragm framework, the thickness of the diaphragm is greatly reduced while the high mechanical strength of the diaphragm is ensured, and the resistance of the diaphragm is further reduced, and then conductive inorganic particles are grown on the surface of the polymer non-woven fabric and in pore channels by adopting an in-situ chemical deposition method. The preparation process is simple, and industrial amplification is easy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hydrogen production by water electrolysis, and in particular relates to a high-efficiency composite diaphragm for hydrogen production by alkaline water electrolysis and a preparation method thereof. Background Art

[0002] As a highly potential energy carrier and raw material, hydrogen energy can be applied to energy, transportation, chemical industry, steel and other fields. Using renewable energy such as solar energy, wind energy, and hydropower to produce hydrogen by electrolysis of water is an efficient hydrogen production strategy with no carbon emissions. Compared with proton exchange membrane (PEM) water electrolysis, anion exchange membrane (AEM) water electrolysis and solid oxide water electrolysis (SOE), alkaline water electrolysis (AWE) has the advantages of low manufacturing cost, high technical reliability and good stability. It is considered to be the only technical solution that can achieve large-scale and low-cost renewable energy water electrolysis hydrogen production. As the core material of alkaline electrolyzer, the diaphragm plays the role of transmitting electrolyte and blocking hydrogen and oxygen gas. Therefore, the performance of the diaphragm has an important influence on the efficiency and safety of the electrolyzer. In the early days, the diaphragm used for alkaline water electrolysis to produce hydrogen was mainly asbestos diaphragm, but asbestos is easy to swell in alkaline electrolyte and is carcinogenic, so it has been gradually eliminated by the market. In recent years, industrial alkaline electrolyzers in my country have begun to generally use woven polyphenylene sulfide diaphragms (i.e., PPS diaphragms). PPS diaphragm has the characteristics of excellent heat resistance, high mechanical strength and excellent electrical properties. It currently occupies more than 90% of the domestic alkaline diaphragm market share. However, in actual applications, it is found that the poor hydrophilicity of PPS diaphragm will cause the internal resistance of the electrolyzer to be too large, the energy consumption of hydrogen production remains high, and it is difficult to reduce the cost of hydrogen production; at the same time, the poor gas barrier performance of the woven structure will lead to reduced hydrogen purity, causing safety hazards. In the case of large-scale application of alkaline water electrolysis to produce hydrogen, economy and safety are the most important considerations. Therefore, it is urgent to develop new diaphragm materials with both low resistance and high gas barrier properties to support the upgrading of alkaline water electrolysis hydrogen production technology and equipment.

[0003] The third generation of organic-inorganic composite diaphragms has low resistance and high gas barrier properties, and is recognized as the future development direction of alkaline hydrogen production diaphragms. However, since the composite diaphragm is a mixture of organic and inorganic components and has a porous structure inside, its mechanical properties are extremely poor; the mechanical strength is usually improved by embedding PPS wire mesh inside the composite diaphragm; however, in order to ensure high mechanical strength, the thickness of the PPS wire mesh usually used is close to the thickness of the diaphragm coating (~300μm). Due to the obvious increase in the thickness of the diaphragm, the diaphragm resistance is also significantly increased, the diaphragm performance is poor, and the energy consumption of the electrolyzer increases. Summary of the invention

[0004] The present disclosure aims to solve at least one of the technical problems existing in the prior art and to provide a high-efficiency composite diaphragm for producing hydrogen by alkaline water electrolysis and a preparation method thereof.

[0005] In one aspect of the present disclosure, a method for preparing a high-efficiency composite diaphragm for producing hydrogen by alkaline water electrolysis is provided, the preparation method comprising:

[0006] S110, dissolving the polymer raw material in a solvent, stirring and mixing, and forming a spinning solution;

[0007] S120, preparing a polymer nonwoven fabric by flash evaporation of the spinning solution;

[0008] S130, soaking the polymer nonwoven fabric in a strong alkali solution, a metal chloride solution or a metal nitrate solution in sequence to form conductive inorganic particles on the surface and inside the pores of the polymer nonwoven fabric;

[0009] S140, repeating step S120 and step S130 multiple times to clean the membrane material and obtain a porous composite membrane.

[0010] Optionally, the step of dissolving the polymer raw material in a solvent, stirring and mixing, and forming a spinning solution comprises:

[0011] Under stirring conditions at 155-165°C, the polymer raw material is dissolved in the solvent, the temperature is raised to 175-185°C and stirred, nitrogen is introduced and pressurized to 10-13MPa, and the temperature is raised to 230-250°C and stirred for 2-4h to form a uniform spinning solution.

[0012] Optionally, the polymer raw material is one or more of polypropylene, polyethylene, and polyamide; and / or,

[0013] The solvent is a mixed solvent of difluoromonochloromethane and tetrafluorodichloroethane.

[0014] Optionally, the step of preparing the polymer nonwoven fabric by flash evaporation of the spinning solution comprises:

[0015] The spinning solution is placed in a decompression chamber and pumped to the spinneret to form a fiber bundle, which is then stretched for the second time. The fiber bundle is evenly unfolded to form a net-like fluffy structure. The unfolded fiber bundle is swung downward and laid on a moving curtain to form a fiber web. After the fiber web is initially shaped by a hot press, it is processed by a hot calender to obtain a polymer non-woven fabric with high mechanical strength.

[0016] Optionally, the polymer non-woven fabric is immersed in the strong alkaline solution, the metal chloride solution or the metal nitrate solution for 2-20 minutes.

[0017] Optionally, the metal chloride is magnesium chloride, and the metal nitrate is magnesium nitrate.

[0018] Optionally, the porous composite membrane has a thickness of 1 μm-80 μm.

[0019] Another aspect of the present disclosure provides a high-efficiency composite diaphragm for producing hydrogen by alkaline water electrolysis, which is prepared by the preparation method described above; wherein the high-efficiency composite diaphragm includes: a polymer non-woven fabric and conductive inorganic particles distributed inside the pores of the polymer non-woven fabric.

[0020] Optionally, the polymer nonwoven fabric has a thickness of 1 μm-50 μm and a pore size range of 0.1 μm-1 μm.

[0021] Optionally, the conductive inorganic particles are one or more metal hydroxides, and have a particle size of 20 nm-200 nm.

[0022] The present disclosure provides a high-efficiency composite diaphragm for producing hydrogen by alkaline water electrolysis and a preparation method thereof, the preparation method comprising: S110, dissolving a polymer raw material in a solvent, stirring and mixing to form a spinning solution; S120, preparing a polymer non-woven fabric from the spinning solution by a flash evaporation method; S130, soaking the polymer non-woven fabric in a strong alkaline solution, a metal chloride solution or a metal nitrate solution in turn, and forming conductive inorganic particles on the surface and inside the pores of the polymer non-woven fabric after calcination; S140, repeating steps S120 and S130 for multiple times, washing the membrane material, and obtaining a porous composite diaphragm. The present disclosure uses a polymer non-woven fabric prepared by a flash evaporation method as a diaphragm skeleton, which effectively ensures the high mechanical strength of the diaphragm while greatly reducing the thickness of the diaphragm, thereby effectively reducing the resistance of the diaphragm; at the same time, an in-situ chemical deposition method is used to grow conductive inorganic particles on the surface and inside the pores of the polymer non-woven fabric, and the preparation process is simple and easy to scale up industrially. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a flowchart of a method for preparing a high-efficiency composite diaphragm for producing hydrogen by alkaline water electrolysis according to an embodiment of the present disclosure;

[0024] Figure 2 This is a schematic flow chart of a method for preparing a high-efficiency composite diaphragm for producing hydrogen by alkaline water electrolysis in Example 1 of the present disclosure;

[0025] Figure 3 is a stress-strain curve diagram of the composite diaphragm obtained in Example 1 of the present disclosure;

[0026] Figure 4 Schematic diagram of the electrolytic hydrogen production performance of the composite membrane obtained in Example 1 of the present disclosure, the commercial composite membrane, and the traditional PPS membrane when applied to the alkaline water electrolysis hydrogen production process. DETAILED DESCRIPTION

[0027] In order to enable those skilled in the art to better understand the technical solution of the present disclosure, the present disclosure is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It should be understood that the specific embodiments described herein are only used to explain the present disclosure and are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.

[0028] like Figure 1 As shown, in one aspect of the present disclosure, a method S100 for preparing a high-efficiency composite diaphragm for producing hydrogen by alkaline water electrolysis is provided, which specifically comprises the following steps S110 to S140:

[0029] S110, dissolving the polymer raw material in a solvent, stirring and mixing, and forming a spinning solution.

[0030] Specifically, under stirring conditions at a first preset temperature, the polymer raw material is dissolved in a solvent, stirred at a second preset temperature, nitrogen is introduced and pressurized to a preset pressure, and the temperature is raised to a third preset temperature and stirred for a preset time to form a uniform spinning solution.

[0031] In some preferred embodiments, the first preset temperature is 155-165°C, the second preset temperature is 175-185°C, the third preset temperature is 230-250°C, the preset pressure is 10-13MPa, and the preset time is 2-4h. That is, under high temperature stirring conditions of 155-165°C, the polymer raw material is dissolved in the solvent, the stirring is reduced and the temperature is raised to 175-185°C, then nitrogen is introduced to pressurize to 10-13MPa, the temperature is continued to rise to 230-250°C, and stirring is continued for 2-4h to form a spinning solution with uniform texture.

[0032] In some preferred embodiments, the first preset temperature is preferably 155°C, 160°C, 165°C; the second preset temperature is preferably 175°C, 180°C, 185°C; the third preset temperature is preferably 230°C, 235°C, 240°C, 245°C, 250°C, the preset pressure is preferably 10MPa, 11MPa, 12MPa, 13MPa, etc., and the stirring time is preferably 2h, 3h, 4h, etc. Of course, the above parameters such as preset temperature and time can be adaptively adjusted according to the selected polymer material, and no specific limitation is made to this.

[0033] In other preferred embodiments, the polymer raw material is one or more of polypropylene, polyethylene, and polyamide, which have high mechanical strength and good hydrophilicity.

[0034] In other preferred embodiments, the solvent is a mixed solvent of difluorochloromethane and tetrafluorodichloroethane, wherein the mass ratio of difluorochloromethane to tetrafluorodichloroethane is (2-4):1, preferably 2:1, 3:1, 4:1, etc.

[0035] S120, preparing a polymer nonwoven fabric by flash evaporation of the spinning solution.

[0036] Specifically, the spinning solution obtained in step S120 is placed in a decompression chamber and pumped to the spinneret for spraying, the solvent evaporates quickly, the polymer solidifies quickly to form a fiber bundle, and then the fiber bundle is stretched twice, the fiber bundle is evenly spread out to form a net-like fluffy structure, the spread fiber bundle swings downward and is laid on the moving curtain to form a fiber net, the fiber net is initially shaped by a hot press, and then processed by a hot rolling mill, the polymer filaments are melted to a certain extent, and when the temperature is lowered, the monofilaments are mostly smooth and irregular band structures, and the whole is evenly distributed, so as to obtain a polymer non-woven fabric with high mechanical strength. The method is easy to operate and reduces production costs.

[0037] In some preferred embodiments, in the hot press, the roller temperature is 140-160°C, for example, preferably 140°C, 150°C, 160°C, etc., and the line speed is 10-13m / min, for example, preferably 10m / min, 11m / min, 12m / min, 13m / min, etc.

[0038] The polymer nonwoven fabric prepared by the flash evaporation method in this embodiment is relatively thin, with a thickness range of only 1 μm-50 μm, for example, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, etc. At the same time, the polymer nonwoven fabric has a porous structure inside, with a pore size range of 0.1 μm-1 μm, for example, 0.1 μm, 0.5 μm, 1 μm.

[0039] S130, soaking the polymer non-woven fabric in a strong alkaline solution, a metal chloride solution or a metal nitrate solution in sequence, and forming conductive inorganic particles on the surface and inside the pores of the polymer non-woven fabric after calcination.

[0040] Specifically, the polymer non-woven fabric is immersed in a strong alkaline solution, a metal chloride solution or a metal nitrate solution for a period of 2-20 minutes, for example, 2 minutes, 5 minutes, 10 minutes, 15 minutes, 20 minutes, etc. The polymer non-woven fabric fully absorbs the solution, so that the inorganic precursor can be evenly distributed on the fibers of the polymer non-woven fabric, and the metal salt is hydrolyzed to form conductive metal hydroxide particles. At the same time, these conductive inorganic particles are deposited on the surface of the polymer non-woven fabric and inside the porous structure through in-situ chemical reactions, thereby improving the hydrophilicity of the non-woven fabric.

[0041] In some preferred implementations, the particle size of the conductive inorganic particles formed in the porous structure of the polymer non-woven fabric is 20 nm-200 nm, for example, 20 nm, 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 200 nm, etc.

[0042] It should be understood that the metal chloride and metal nitrate in step S130 should be precursors of the conductive inorganic particles in the composite membrane, that is, the metal chloride may preferably be magnesium chloride, and the metal nitrate may preferably be magnesium nitrate. Of course, potassium hydroxide and the like may also be preferred.

[0043] It should also be understood that the strong alkaline solution in this embodiment can be a solution of sodium hydroxide, potassium hydroxide, etc., and there is no specific limitation on this.

[0044] S140, repeating step S120 and step S130 for multiple times (3-6 times), washing the membrane material with deionized water to obtain a porous composite membrane.

[0045] In this embodiment, a polymer non-woven fabric prepared by a flash evaporation method is used as a composite diaphragm skeleton, which greatly reduces the thickness of the diaphragm (for example, the thickness of the composite diaphragm is preferably 1 μm-80 μm) while effectively ensuring the high mechanical strength of the diaphragm, thereby effectively reducing the resistance of the diaphragm; at the same time, an in-situ chemical deposition method is used to grow conductive inorganic particles on the surface of the polymer non-woven fabric and inside the pores, which effectively improves the conduction efficiency of hydroxide ions and further reduces the resistance of the diaphragm; the composite diaphragm proposed in the present invention has the characteristics of high mechanical strength and low resistance, and is therefore more adaptable to the electrolyzer, and can effectively reduce the energy consumption of hydrogen production in the electrolyzer, and can completely replace the traditional PPS diaphragm for application in a variety of different water electrolysis hydrogen production scenarios, showing great application potential.

[0046] Another aspect of the present disclosure provides a high-efficiency composite diaphragm for producing hydrogen by alkaline water electrolysis, which is prepared by the preparation method described above. Please refer to the above description for the specific process, which will not be repeated here.

[0047] Specifically, the high-efficiency composite separator includes a polymer non-woven fabric and conductive inorganic particles distributed inside the pores of the polymer non-woven fabric.

[0048] In some preferred embodiments, the polymer nonwoven fabric has a thickness of 1 μm-50 μm, for example, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, etc. The polymer nonwoven fabric has a porous structure with a pore size ranging from 0.1 μm to 1 μm, for example, 0.1 μm, 0.5 μm, 1 μm.

[0049] In other preferred embodiments, the conductive inorganic particles are one or more of metal hydroxides, and the preferred metal cation is Mg 2+The particle size of the inorganic conductive particles is 20 nm to 200 nm, for example, 20 nm, 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 200 nm, etc., more preferably, 100 nm.

[0050] In this embodiment, the composite membrane is applied to the production of hydrogen by alkaline water electrolysis, including the water electrolysis hydrogen production reaction process and the water electrolysis oxygen production reaction process, so that the overall performance of the alkaline electrolyzer can be effectively improved.

[0051] The following will further illustrate the high-efficiency composite diaphragm for producing hydrogen by alkaline water electrolysis in conjunction with specific examples:

[0052] Example 1

[0053] The method for preparing a high-efficiency composite diaphragm for producing hydrogen by alkaline water electrolysis in this example includes the following steps: Figure 2 As shown:

[0054] S1. Dissolve 120g of polyethylene raw material in a solvent containing chlorodifluoromethane and dichlorotetrafluoroethane at a mass ratio of 3:1 at 160°C under stirring; raise the temperature to 180°C under stirring, then introduce nitrogen and pressurize to 12MPa, continue to raise the temperature to 240°C, and continue stirring for 3h to form a spinning solution with uniform texture.

[0055] S2. The spinning solution passes through a decompression chamber and is pumped to the spinneret for spraying. The solvent in the spinning solution evaporates rapidly, and the polymer solidifies rapidly to form a fiber bundle. The fiber bundle is then guided to the air amplifier by a steering plate for secondary stretching. The fiber bundle is evenly unfolded into a net-like fluffy structure. The unfolded fiber bundle swings downward and is laid on a moving curtain. After the fiber web is initially shaped by a hot press, the fabric is introduced into a hot rolling mill (roller temperature 150°C, line speed 12m / min) through a cloth guide roller to prepare a polyethylene non-woven fabric with high mechanical strength.

[0056] S3. Soak the obtained polyethylene nonwoven fabric in a strong alkaline solution (sodium hydroxide solution) for 10 minutes; and then soak it in a metal chloride solution (magnesium chloride solution) for 10 minutes.

[0057] S4. The above steps S2 and S3 are cycled five times in sequence, and the membrane material obtained in the above steps is washed with deionized water to obtain a porous composite diaphragm. The thickness of the porous composite diaphragm is 60 μm.

[0058] Furthermore, if Figure 3 As shown, the mechanical strength of the porous composite membrane obtained in Example 1 is 56.1 MPa.

[0059] Furthermore, if Figure 4As shown, the porous composite membrane obtained in Example 1 was compared with the traditional PPS membrane and the commercial composite membrane in the process of alkaline water electrolysis to produce hydrogen. The results show that under the same current density, the voltage of the homemade composite membrane in Example 1 is significantly lower than that of the traditional PPS membrane and the commercial composite membrane, and the performance of water electrolysis to produce hydrogen is better, showing good industrial application potential.

[0060] The present disclosure provides a high-efficiency composite diaphragm for producing hydrogen by alkaline water electrolysis and a preparation method thereof, which has the following beneficial effects compared with the prior art:

[0061] First, the preparation process of the composite diaphragm disclosed in the present invention is simple and easy to scale up industrially. By using the polymer non-woven fabric prepared by the flash evaporation method as the diaphragm skeleton, the thickness of the diaphragm is greatly reduced while effectively ensuring the high mechanical strength of the diaphragm, thereby effectively reducing the resistance of the diaphragm; at the same time, the in-situ chemical deposition method is used to grow conductive inorganic particles on the surface of the polymer non-woven fabric and inside the pores, which effectively improves the conduction efficiency of hydroxide ions and further reduces the resistance of the diaphragm.

[0062] Second, the composite diaphragm proposed in the present invention is relatively thin, has the characteristics of high mechanical strength and low resistance, is more adaptable to the electrolyzer, and can effectively reduce the energy consumption of hydrogen production in the electrolyzer. It can completely replace the traditional PPS diaphragm and be applied to a variety of different water electrolysis hydrogen production scenarios, showing great application potential.

[0063] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present disclosure, but the present disclosure is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and substance of the present disclosure, and these modifications and improvements are also considered to be within the scope of protection of the present disclosure.

Claims

1. A method for preparing a high-efficiency composite diaphragm for producing hydrogen by alkaline water electrolysis, characterized in that: The preparation method comprises: S110, dissolving the polymer raw material in a solvent, stirring and mixing, and forming a spinning solution; S120, preparing a polymer nonwoven fabric by flash evaporation of the spinning solution; S130, soaking the polymer non-woven fabric in a strong alkali solution, a metal chloride solution or a metal nitrate solution in sequence, and forming conductive inorganic particles on the surface and inside the pores of the polymer non-woven fabric after calcination; S140, repeating step S120 and step S130 multiple times to clean the membrane material and obtain a porous composite membrane.

2. The preparation method according to claim 1, characterized in that: The step of dissolving the polymer raw material in a solvent, stirring and mixing, and forming a spinning solution comprises: Under stirring conditions at 155-165°C, the polymer raw material is dissolved in the solvent, the temperature is raised to 175-185°C and stirred, nitrogen is introduced and pressurized to 10-13MPa, and the temperature is raised to 230-250°C and stirred for 2-4h to form a uniform spinning solution.

3. The preparation method according to claim 1, characterized in that: The polymer raw material is one or more of polypropylene, polyethylene, and polyamide; and / or, The solvent is a mixed solvent of difluoromonochloromethane and tetrafluorodichloroethane.

4. The preparation method according to claim 1, characterized in that: The method of preparing the polymer nonwoven fabric by flash evaporation of the spinning solution comprises: The spinning solution is placed in a decompression chamber and pumped to the spinneret to form a fiber bundle, which is then stretched for the second time. The fiber bundle is evenly unfolded to form a net-like fluffy structure. The unfolded fiber bundle is swung downward and laid on a moving curtain to form a fiber web. After the fiber web is initially shaped by a hot press, it is processed by a hot calender to obtain a polymer non-woven fabric with high mechanical strength.

5. The preparation method according to claim 1, characterized in that: The polymer nonwoven fabric is immersed in the strong alkali solution, the metal chloride solution or the metal nitrate solution for 2-20 minutes.

6. The preparation method according to claim 1, characterized in that: The metal chloride is magnesium chloride, and the metal nitrate is magnesium nitrate.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The thickness of the porous composite membrane is 1 μm-80 μm.

8. A high-efficiency composite diaphragm for producing hydrogen by alkaline water electrolysis, characterized in that: The high-efficiency composite diaphragm for producing hydrogen by alkaline water electrolysis is prepared by the preparation method according to any one of claims 1 to 7; wherein, The high-efficiency composite diaphragm comprises: polymer non-woven fabric and conductive inorganic particles distributed inside the pores of the polymer non-woven fabric.

9. The high-efficiency composite diaphragm for producing hydrogen by alkaline water electrolysis according to claim 8, characterized in that: The polymer nonwoven fabric has a thickness of 1 μm-50 μm and a pore size range of 0.1 μm-1 μm.

10. The high-efficiency composite diaphragm for producing hydrogen by alkaline water electrolysis according to claim 8, characterized in that: The conductive inorganic particles are one or more of metal hydroxides, and the particle size is 20nm-200nm.

Citation Information

Cited By

  • High-performance alkaline water electrolysis composite diaphragm as well as preparation method and application thereof

    CN120041884A